Migraine and the Scope of Homeopathy - Wandile, Pranali M. (Homœopathic Links, 2017)
Migraine is usually a genetic disorder. In the United States, every 10 seconds someone with a migraine goes to the emergency room. Approximately 1.2 million annual visits to the emergency room occur due to acute migraine attacks. About 90% of migraine patients have a family history of this illness. More than 90% of sufferers are unable to work or function normally during their migraine episode, affecting their quality of life and medical expenditure. While the majority of patients experience attacks once or twice a month, more than four million people suffer due to a chronic migraine with at least 15 migraine days per month. Migraine is often undiagnosed and undertreated and remains a poorly understood disease. In spite of the high prevalence of migraine and its effects on patients, research into migraine is still underfunded. In this article, the author reviewed facts about migraine, the best possible suggested treatments and the scope of homeopathy for its treatment. More research and clinical trials with improved trial designs are warranted. Publications of large numbers of homeopathic case studies worldwide, long-term observational studies of treated migraine patients having no further migraine recurrences are needed to see the role of homeopathy for the complete cure.
Keywords: homeopathy; migraine; double-blind placebo-controlled trials